Antioxidant Supplementation in the Treatment of Aging-Associated Diseases - Conti, Valeria; Izzo, Viviana; Corbi, Graziamaria; Russomanno, Giusy; Manzo, Valentina; De Lise, Federica; Di Donato, Alberto; Filippelli, Amelia (Frontiers in Pharmacology, 2016)
Oxidative stress is generally considered an imbalance between pro- and antioxidants species, which often results into indiscriminate and global damage at the organismal level. Elderly people are more susceptible to oxidative stress and this depends, almost in part, from a decreased performance of their endogenous antioxidant system. As many studies reported an inverse correlation between systemic levels of antioxidants and several diseases, primarily cardiovascular diseases, but also diabetes and neurological disorders, antioxidant supplementation has been foreseen as an effective preventive and therapeutic intervention for aging-associated pathologies. However, the expectations of this therapeutic approach have often been partially disappointed by clinical trials. The interplay of both endogenous and exogenous antioxidants with the systemic redox system is very complex and represents an issue that is still under debate. In this review a selection of recent clinical studies concerning antioxidants supplementation and the evaluation of their influence in aging-related diseases is analyzed. The controversial outcomes of the antioxidants supplementation therapy that might partially depend, among others, from an underestimation of the patient specific metabolic demand and genetic background, are presented.